2013
DOI: 10.1016/j.jallcom.2012.01.095
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the shape memory effect in a NiTi nano model system

Abstract: The shape memory behavior of a NiTi nanoparticle is analyzed by molecular dynamics simulations. After a detailed description of the equilibrium structures of the used model potential, the multi variant martensitic ground state, which depends on the geometry of the particle, is discussed. Tensile load is applied, changing the variant configuration to a single domain state with a remanent strain after unloading. Heating the particle leads to a shape memory effect without a phase transition to the austenite, but … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…This difference is mainly due to size effects and consideration of the single crystal (in the simulations) vs. the polycrystalline (in the experiment) NiTi SMA samples; this is addressed in detail in the following sections. Significant size effects have been reported extensively, [25,27,28,30,61] where it is also demonstrated that the presence of defects such as free surfaces can appreciably alter the martensite transformation start Size effects are demonstrated in Figure 3 and some relevant results (evolution of microstructure at different temperatures and sizes) are documented in the supplementary material. Figure 3 shows the variation of martensite phase fraction with respect to temperature for different size of NiTi films.…”
Section: Figure-2mentioning
confidence: 82%
“…This difference is mainly due to size effects and consideration of the single crystal (in the simulations) vs. the polycrystalline (in the experiment) NiTi SMA samples; this is addressed in detail in the following sections. Significant size effects have been reported extensively, [25,27,28,30,61] where it is also demonstrated that the presence of defects such as free surfaces can appreciably alter the martensite transformation start Size effects are demonstrated in Figure 3 and some relevant results (evolution of microstructure at different temperatures and sizes) are documented in the supplementary material. Figure 3 shows the variation of martensite phase fraction with respect to temperature for different size of NiTi films.…”
Section: Figure-2mentioning
confidence: 82%
“…An effective MD simulation framework for NiTi binary alloy based on the Finnis-Sinclair many-body interatomic potential has been proposed and examined in detail [11,23,24,31,39,44,45,53,[57][58][59]. For self-containment, a brief and relevant description of this semiempirical interatomic MD potential is provided here, yet more detailed information can be found elsewhere [11,23,24,31,39,44,45,53,[57][58][59]. Lai and Liu [53] developed this semiempirical interatomic potential based on experimental data and first principal calculations.…”
Section: Interatomicmentioning
confidence: 99%
“…A very recent study based on classical MD shows size effects at the atomic scale, in both the austenitic and martensitic phase transformation process of NiTi nanoparticles [25,31]. Experimental studies at the nanometer and micrometer length scales, for different structures such as thin films [30,36], nanoparticles [25,31], and nanopillars [23,24,44], report the presence of strong size effects on the thermally induced martensitic phase transformation process. They mainly address surface and/or size effects in (a) transformation induced morphologies or microstructure of NiTi and (b) phase transformation process.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Mutter et al [22] confirmed the experimentally knowing dependence of transition temperatures on composition using the potential developed by Lai et al [19]. The thermally induced austenitic phase transition [23] and the shape memory effect in NiTi nanoparticles [24] were studied using the same potential.…”
Section: Introductionmentioning
confidence: 81%